Through the history of the Cold War : the correspondence of George F. Kennan and John Lukacs - Kennan, George F. (George Frost), 1904-2005 (EBL-Schweitzer, 2010)
Presented with an introduction by John Lukacs, the letters in this volume reveal new dimensions in George Kennan's thinking about America and its future and illuminate the political--and spiritual--philosophies that both authors shared as they wrote about a world transformed by war and the clash of ideologies that defined the twentieth century.